Joe Pickett. Season 2 [videorecording (DVD)] - Chbosky, Stacy; Box, C. J.; Gómez, Isaac; Greaves, Nelson; Box, C. J.; Dowdle, Drew; Dowdle, Drew; Dowdle, Drew; Dowdle, John Erick; Dowdle, John Erick; Dowdle, John Erick; Dorman, Michael, 1981-; et al. (Paramount, 2023)
One year after the violent attack on the Pickett family, Joe and Marybeth try to pick up the pieces and move forward together. Joe journeys deep into the forest on the mysterious Bermuda Mountain in search of a lost hunter and makes a grim discovery. Meanwhile, Marybeth throws herself into her legal work in an effort to forget the loss her family suffered. This three-disc DVD collection includes all ten episodes plus deleted scenes.